2+3(-7x-1)=-5(-x-7)=8

Simple and best practice solution for 2+3(-7x-1)=-5(-x-7)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+3(-7x-1)=-5(-x-7)=8 equation:



2+3(-7x-1)=-5(-x-7)=8
We move all terms to the left:
2+3(-7x-1)-(-5(-x-7))=0
We add all the numbers together, and all the variables
3(-7x-1)-(-5(-1x-7))+2=0
We multiply parentheses
-21x-(-5(-1x-7))-3+2=0
We calculate terms in parentheses: -(-5(-1x-7)), so:
-5(-1x-7)
We multiply parentheses
5x+35
Back to the equation:
-(5x+35)
We add all the numbers together, and all the variables
-21x-(5x+35)-1=0
We get rid of parentheses
-21x-5x-35-1=0
We add all the numbers together, and all the variables
-26x-36=0
We move all terms containing x to the left, all other terms to the right
-26x=36
x=36/-26
x=-1+5/13

See similar equations:

| -5u+13u=3u+-12+42+5 | | 10=6t-2 | | 23=4t+5 | | 0.04x+1=1.2 | | 32x+1=1/2187 | | k/6+3=18 | | __13y-__12=__16y | | 144-2n=106 | | -9x-12=-75 | | (x+1)=2x-(4-x) | | 8/9*216=r | | 1.2-0.3x=1.5 | | -99610=1700-55p | | -6=g/2 | | -5x+0.9=15.9 | | 8/9r=24 | | 3/5y+3/8=1/4y+1/8 | | 2x-24=-4x+8 | | -8(x+2)/(x^2+4x+5)^2=0 | | 33(x-2)-13=43 | | 30x^2-35x=-10 | | 5(1-x)=3 | | 3/7x=300 | | 16x-16x-2=-8 | | X^2+12x-13=7 | | 35+(x+5)=90 | | 1/2n-6=8n | | 35+x+5=90 | | 0=30x^2-35x+10 | | (x+2)+35=90 | | 28x+5=26x+(-9) | | (x+2)+35= 90 |

Equations solver categories